Etnomatematika: Eksplorasi Objek Dan Aktivitas Matematika Pada Bentuk Jajanan Tradisional Masyarakat Lombok, Indonesia - Rahmasari , Aulia; Al Kusaeri , Al Kusaeri; Mahfudy, Sofyan (Jurnal of Math Tadris, 2022)
This study aims to determine the traditional snacks of the Sakra community, the mathematical objects contained in the traditional snacks of the Sakra people, and the mathematical activities contained in the process of making and selling traditional snacks of the Sakra people. In this study, the researcher used a qualitative approach with an ethnographic type of approach. This research was conducted in Sakra District, East Lombok Regency, NTB, especially in the area of ​​Sakra traditional snack traders. Based on the results of the analysis of the discussion in this study, it can be concluded that temerodok and jaje kaok are traditional snacks from Sakra village. These two snacks have an important role in the customs of the Sakra community and also in helping the economy of the Sakra village community. The results of the identification of the traditional forms of the Sakra people's snacks (temerodok and jaje kaok) can be concluded that there are mathematical objects in these two snacks, namely crescent moons, ellipses, parabolic curves, and rectangles and blocks. And based on the results of the analysis of the Sakra community's activities in making traditional snacks, forms/patterns of snacks and in the process of selling traditional snacks, it can be concluded that there are mathematical activities in the two traditional snacks, namely counting activities, measuring activities, designing activities, and explaining activities.